Problem in Atypical Squamous Cells - Suwicha Chittithaworn (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
It is well known that cervical cancer is the most common cancer affecting women in developing countries, including Thailand. The incidence of cervical cancer did not reduce satisfactorily due to insufficient screening. Pap smear is the easy, widely used and economical screening method. Bethesda system has been used for reporting since 1988(1). This article will cover only about atypical squamous cell which nowadays report by Bethesda 2001(2).